2017
DOI: 10.1159/000470901
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Research on Latent Esophageal Motility Disorders in Dysphagia Patients

Abstract: Background/Aims: High-resolution manometry (HRM) has been applied to assess esophageal motility disorders. However, the frequency and types of motility disorders in patients with dysphagia, which are frequently seen in clinical practice, are not clear. We evaluated latent esophageal motility disorders associated with dysphagia. Methods: The study included patients without erosive esophageal mucosal damage and with dysphagia symptoms refractory to at least 8 weeks of standard-dose proton pump inhibitors. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…There are six limitations to this study, the first of which concerns the possibility of bias in the sub‐classification of esophageal motility disorders in the enrolled patients. In the studies to date that have investigated the sub‐classification of esophageal motility disorders in patients with dysphagia in Japan, 6,17,18 the results are consistent with those of our study cohort. Therefore, one would expect no major biases in registered patients with esophageal motility disorders.…”
Section: Discussionsupporting
confidence: 89%
“…There are six limitations to this study, the first of which concerns the possibility of bias in the sub‐classification of esophageal motility disorders in the enrolled patients. In the studies to date that have investigated the sub‐classification of esophageal motility disorders in patients with dysphagia in Japan, 6,17,18 the results are consistent with those of our study cohort. Therefore, one would expect no major biases in registered patients with esophageal motility disorders.…”
Section: Discussionsupporting
confidence: 89%
“…Another study suggested that in the older population (> 60 years) with esophageal symptoms, the reduction in UES pressure, distal esophageal motility, and peristaltic velocity might be correlated with esophageal symptoms using HREM. 20 Nevertheless, Jadiri and colleagues reported no significant difference between young and old patients with dysphagia. 21 Furthermore, we found no correlation between smoking status and alcohol and opiate consumption and EMDs prevalence (P > 0.05).…”
Section: Resultsmentioning
confidence: 96%
“…We speculated that the visceral sensitivity may be associated with high UES pressure, but the results of the present study did not show a significant difference in the S/S genotype between the subgroups. For the complexity of the formation of UES pressure [24] and the mechanism of globus, this hypothesis requires further exploration. We observed that antidepressants decreased UES pressure.…”
Section: Discussionmentioning
confidence: 99%